The earth's electric field : sources from sun to mud - Kelley, Michael C. (Elsevier, 2013)
The Earth's Electric Field provides you with an integrated and comprehensive picture of the generation of the terrestrial electric fields, their dynamics and how they couple/propagate through the medium. The Earth's Electric Field provides basic principles of terrestrial electric field related topics, but also a critical summary of electric field related observations and their significance to the various related phenomena in the atmosphere. For the first time, Kelley brings together information on this topic in a coherent way, making it easy to gain a broad overview of the cri.